Basic characteristics and environmental impact of iron ore tailings - Wang, Changlong; Jing, Jianlin; Qi, Yang; Zhou, Yongxiang; Zhang, Kaifan; Zheng, Yongchao; Zhai, Yuxin; Liu, Feng (Frontiers in Earth Science, 2023)
Introduction: In our study, various test methods were adopted to explore the mineralogical characteristics, grindability, particle morphology, particle size distribution, and environmental leaching toxicity of iron ore tailings (lOTs). Methods: The methods include petrographic analysis, X-ray diffraction (XRD), scanning electronic microscopy (SEM), synchronous thermal analyzer (DSC-TGA), electron probe X-ray microanalyser (EPMA), and synthetic precipitation leaching Procedure (SPLP). Results: The results show that the used IOTs contained 14.54% iron which was mainly stored in magnetite and pyrite. The content of iron silicate accounted for 11.82% of the total iron content. Most of it existed in silicate minerals, including grunerite and hornblende. A small amount of iron was contained in biotite, chlorite and augite. Besides, the grindability of lOTs was much better than that of granulated blast furnace slag (GBFS). After grinding for 140 min, the mass fraction of lOTs particles with the particle size less than 5 um was 44.19%. These particles could be used to fill in the voids in the cement-powder-packed structure. lOTs also contained a large number of submicron and nanoscale particles. Discussion: With great strength and environmental friendliness, the composite cementitious material (CCM) prepared from lOTs can be well applied to the building material field and environmental remediation.